PENERAPAN MEDIA PEMBELAJARAN VIDEO DAN PRAKTEK PADA MATA PELAJARAN FIQH MATERI TATACARA PELAKSANAAN HAJI DAN UMRAH KELAS VIII MTs MADINATUSSALAM PERCUT SEI TUAN - Wulandari, Susi (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This study aims to describe student learning outcomes before and after using video learning media and practice on the subject of Islamic Civilization History, Hajj and Umrah Procedures, and to describe the successful implementation of video media and practice in learning Fiqh for Hajj and Umrah Procedures at MTs Madinatussalam Percut Sei Sir. The population in this study were all students of class VIII. The research sample was determined as many as 28 students. The sample was determined using a purposive technique. This research method is an experimental method. The data collection tool used was a test of learning outcomes of Fiqh, the material for Hajj and Umrah procedures in the form of multiple choice objective questions of 20 questions that were tested before and after participating in learning using video and practical media. The conclusions obtained from this study are: student learning outcomes before using video learning media and practice on the subject of Fiqh, Hajj and Umrah Procedures in MTs Madinatussalam Percut Sei Tuan is 63.39 with the highest score of 80, moderate 60, and the lowest 40 The improvement of student learning outcomes in class VIII in the subject of Fiqh, Hajj and Umrah Procedures material at MTs Madinatussalam Percut Sei Tuan after implementing learning using video learning media and practice was 80.17 with the highest score of 95, moderate 80, and the lowest was 65. Successful implementation Video media and practice in learning Fiqh on Hajj and Umrah Procedures at MTs Madinatussalam Percut Sei Tuan reached 59.5% including the category of fairly good influence. That is, the use of power point media helps improve learning outcomes of Fiqh by 47.31%, including in the category of moderate improvement.